2019
DOI: 10.1523/jneurosci.2130-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Zn2+Signaling Facilitates Mossy Fiber Input-Induced Heterosynaptic Potentiation of Direct Cortical Inputs in Hippocampal CA3 Pyramidal Cells

Abstract: Repetitive action potentials (APs) in hippocampal CA3 pyramidal cells (CA3-PCs) backpropagate to distal apical dendrites, and induce calcium and protein tyrosine kinase (PTK)-dependent downregulation of Kv1.2, resulting in long-term potentiation of direct cortical inputs and intrinsic excitability (LTP-IE). When APs were elicited by direct somatic stimulation of CA3-PCs from rodents of either sex, only a narrow window of distal dendritic [Ca 2ϩ ] allowed LTP-IE because of Ca 2ϩ-dependent coactivation of PTK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 63 publications
5
30
0
Order By: Relevance
“…Next, we examined MF-induced LTP-IE of CA3-PCs in CA3- Kcna2+/− mice and their WT littermates ( f-Kcna2 ) in the third postnatal week because Cre/loxP recombination is detectable on postnatal day 14 in the CA3 region (Nakazawa et al, 2002). In addition, we previously reported that the degree of LTP-IE is not different between the third and 12th postnatal week mice (Eom et al, 2019). LTP-IE was assessed by input conductance (G in ) and first spike latency, which were measured as in Figure 1B.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Next, we examined MF-induced LTP-IE of CA3-PCs in CA3- Kcna2+/− mice and their WT littermates ( f-Kcna2 ) in the third postnatal week because Cre/loxP recombination is detectable on postnatal day 14 in the CA3 region (Nakazawa et al, 2002). In addition, we previously reported that the degree of LTP-IE is not different between the third and 12th postnatal week mice (Eom et al, 2019). LTP-IE was assessed by input conductance (G in ) and first spike latency, which were measured as in Figure 1B.…”
Section: Resultsmentioning
confidence: 85%
“…Insufficiency of Kv1.2 can be induced not only by genetic mutation but also by repetitive stimulation of afferent MFs or the soma of a CA3-PC. The latter results in a decrease in input conductance and enhanced E-S coupling of PP synaptic inputs, collectively referred to as long-term potentiation of intrinsic excitability (LTP-IE) (Hyun et al, 2013; Hyun et al, 2015; Eom et al, 2019). Notably, LTP-IE enhances PP-EPSPs but not PP-EPSCs, supporting the notion that it is attributed to intrinsic excitability changes of dendrites (Hyun et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations